-4y+3=-3(2y+5)

Simple and best practice solution for -4y+3=-3(2y+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4y+3=-3(2y+5) equation:


Simplifying
-4y + 3 = -3(2y + 5)

Reorder the terms:
3 + -4y = -3(2y + 5)

Reorder the terms:
3 + -4y = -3(5 + 2y)
3 + -4y = (5 * -3 + 2y * -3)
3 + -4y = (-15 + -6y)

Solving
3 + -4y = -15 + -6y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '6y' to each side of the equation.
3 + -4y + 6y = -15 + -6y + 6y

Combine like terms: -4y + 6y = 2y
3 + 2y = -15 + -6y + 6y

Combine like terms: -6y + 6y = 0
3 + 2y = -15 + 0
3 + 2y = -15

Add '-3' to each side of the equation.
3 + -3 + 2y = -15 + -3

Combine like terms: 3 + -3 = 0
0 + 2y = -15 + -3
2y = -15 + -3

Combine like terms: -15 + -3 = -18
2y = -18

Divide each side by '2'.
y = -9

Simplifying
y = -9

See similar equations:

| .60(z-300)+.05z=.70z-205 | | 7c^2-49c+70=0 | | 3s-12s=63 | | 2x^2+9=41 | | logx=2.0832 | | 9x-(3x+8)=7x-10 | | 7-3n=n-4(2+n) | | -10=2+3x | | 3-21=6a | | 13-3b+5=13 | | -30=14x-9x | | -3y-4=6y-19 | | 5x^2+3x-8= | | 8(2x-10)-3=8(x-7)+(5) | | 8m+4m=108 | | 9t^2+171t+162= | | 5x^2-3x+3= | | 6p^2-32p+5=0 | | 2(x+3)(x-1)=176 | | 4x-4=-6 | | x^3+x^2-81x-81=0 | | 3x-9+4x=9 | | .4(2m-10)=.6m+10 | | y=-0.5(1)+1.5 | | 63-63x=(8x+1)(x-1) | | X-39=-19 | | 2(-7)+14= | | .3y=2 | | -17-2*x=6-x | | 4.5r-18=-3r+-4.5 | | -6x-2=-52 | | r+.12=.2 |

Equations solver categories